Volatile Fatty Acids and Methane Profile of Dairy Cattle Ruminal Fluid was Gived Legumes in Ration Based on Synchronization Protein-Energy Index - Afduha Nurus Syamsi; Triana Yuni Astuti; Pramono Soediarto (Buletin Peternakan, 2018)
An experiment was aimed to assess the use of the legumes as a source of protein feedstuff and levels of protein-energy synchronization (PES) index in the diet of dairy cattles on volatile fatty acids (VFA) and methane (CH4) profile. The research was applied in In vitro techniques used a completely randomized design (CRD), with factorially pattern (2x3), the first factor was the two species of legumes (Sesbania and Leucaena) and the second factor was the three level of the PES index (0.4, 0.5, and 0.6), there were 6 treatment combinations and each was 4 replicates. The results showed that interaction between legumes with PES index was not significantly affected (P>0.05) on all variable. Legumes was not significantly affected (P>0.05) on all variables and PES index was significantly affected (P<0.05) on propionate, A:P ratio, and methane. The study concluded that the use of turi and lamtoro leaves combined with the protein-energy synchronization index (PES) at medium level (0.5) could increasing the production of VFA, especially propionate, suppressing A:P ratio and decreasing methane production.